Value for all? Dynamics of partnership formation in occupational healthcare collaboration - Anna-Aurora Kork; Inka Koskela; Merja Turpeinen (Finnish Social and Health Informatics Association, 2021)
Interorganizational relationships take advantages of surrounding networks to create value. However, there is little processual understanding of how cooperative partnerships 'work' in healthcare collaboration. From the value creation perspective, their mobilization, management and maintenance are challenging. To understand the value of cooperative partnerships, we explore the dynamics of partnership formation in occupational healthcare collaboration. The empirical data is based on a two-year qualitative case study examining e-value co-creation in healthcare. The research data was obtained through a participatory action research method. We facilitated and followed up a developmental process of the partnership between an occupational health service company and its customer organization. This partnership aimed to add strategic value through the co-creation method to improve the well-being of employees and to promote eHealth solutions. In analyzing the data, we adopted a process orientation that allowed us to explore dynamics in partnership formation and its e-value co-creation. We used Ring and Van de Ven's [1] framework to examine how cooperative interorganizational relationship develops through the stages of negotiation, commitment and execution. Our longitudinal case study analysis reveals how interaction, mutual sensemaking and institutional logics affect partnership and its value creation. The results show that the formation of a cooperative partnership is a challenging inter-organizational learning process. Our study demonstrates three tensions characterizing the dynamics of partnership: asymmetrical roles and positions between partners (customer and service provider) in co-creation, exploitation of institutionalized practices versus the exploration of new methods for collaboration, and tradeoffs between the operational logic and the co-creation logic. To create value for all in cooperative partnership, we emphasize the necessity of dialogue, mutual trust, interorganizational learning and processual feedback of accomplishments. At its best, cooperative partnership in healthcare collaboration can challenge existing practices of service provision and develop new concepts, roles and tools to promote health and well-being at workplaces through co-creation as a working method in occupational health collaboration.